Controlling immigration through criminal law : European and comparative perspectives on "crimmigration" - Gatta, Gian Luigi; Mitsilegas, Valsamis, 1971-; Zirulia, Stefano (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book provides a systematic and comprehensive overview of the increased role of criminal law in managing migration, from a European, domestic and comparative law perspective. The contributors critically engage with the current trends leading to the criminalisation of irregular migrants, asylum seekers and those who engage in "humanitarian smuggling" and the national and common policies calling for a broader use of criminal law measures and the like. The chapters explore the measures used to protect borders and their impact in terms of effectiveness and their ability to strike a fair balance between security and the protection of human rights. The contributors to the book cover a range of disciplines within law, human rights and criminology resulting in a broad understanding of the issues at play"--
Introduction / Gian Luigi Gatta, Valsamis Mitsilegas and Stefano Zirulia -- Assessing migration management and the role of criminal law / Elspeth Guild -- The criminalisation of migration in the law of the European Union : challenging the preventive paradigm / Valsamis Mitsilegas -- Global trends in 'crimmigration' policies : from the EU to the USA / Gian Luigi Gatta -- The connections between migration, crime, and punishment : historical and sociological questions / Dario Melossi -- Current trends, numbers and routes in EU migrations : is existing legislation creating more irregularity? / Maria Giovanna Manieri -- Crimmigration in Spain / José A Brandariz -- Ethnicity based immigration checks : crimmigration and the how of immigration and border control / Maartje van der Woude -- Crimmigration in Greece : a story of exceptional derogations from the rule of law within a permanent situation of emergency / Nikolaos Chatzinikolaou -- Immigration detention between law and practice in Italy : managing the border through arbitrary detention / Francesca Cancellaro -- Detention as a tool of immigration and asylum enforcement in the EU / Justine N Stefanelli -- Is that a smuggler? : the blurring line between facilitating illegal immigration and providing humanitarian assistance at the European borders / Stefano Zirulia -- Reversing the perspective : criminal responsibility of Italian authorities for human rights violations in Libya? / Luca Masera.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Emigration and immigration law -- European Union countries -- Criminal provisions; Emigration and immigration law -- Criminal provisions; Human smuggling -- Law and legislation -- European Union countries; Illegal aliens; International criminal law; Electronic books